AGBL4 promotes malignant progression of glioblastoma via modulation of MMP-1 and inflammatory pathways - Zhang, Shuai; Cheng, Lilin; Su, Yandong; Qian, Zhongrun; Wang, Zhen; Chen, Chao; Li, Rong; Zhang, Aikang; He, Jiawei; Mao, Jiangxin; Wang, Hongxiang; Chen, Juxiang (Frontiers in Immunology, 2024)
Introduction Glioblastoma multiforme (GBM), the most common primary malignant brain tumor, is notorious for its aggressive growth and dismal prognosis. This study aimed to elucidate the molecular underpinnings of GBM, particularly focusing on the role of AGBL4 and its connection to inflammatory pathways, to discover viable therapeutic targets. Methods Single-cell sequencing was utilized to examine the expression levels of AGBL4 and functional assays were performed to assess the effects of AGBL4 modulation. Results Our findings identified the significant upregulation of AGBL4 in GBM, which correlated with adverse clinical outcomes. Functional assays demonstrated that AGBL4 knockdown inhibited GBM cell proliferation, migration, and invasion and influenced inflammatory response pathways, while AGBL4 overexpression promoted these activities. Further investigation revealed that AGBL4 exerted its oncogenic effects through modulation of MMP-1, establishing a novel regulatory axis critical for GBM progression and inflammation. Discussion Both AGBL4 and MMP-1 may be pivotal molecular targets, offering new avenues for targeted therapy in GBM management.